2011
DOI: 10.1097/aud.0b013e3182291f94
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Hearing Aids: Patterns of Use and Determinants of Nonregular Use

Abstract: Overall, the present study provides evidence of gender-specific factors that influence hearing aid use patterns in men and women and of groups at higher risk for nonregular hearing aid use. Men with steeper audiogram slopes and the other subgroups of men and women with an increased risk for nonregular use should given particular attention when fitting their aids. As common risk factors for nonregular use, poor handling and low satisfaction should be addressed during the fitting process for all users. Further r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 49 publications
1
29
0
2
Order By: Relevance
“…Perhaps there was more room for improvement because HA use among these men was relatively low. This line of reasoning is in accordance with Staehelin et al (2011) who found that irregular use was significantly more likely in men compared with women. To our knowledge, other studies on interventions improving HA use do not report gender differences in HA outcomes.…”
Section: Control Groupsupporting
confidence: 90%
“…Perhaps there was more room for improvement because HA use among these men was relatively low. This line of reasoning is in accordance with Staehelin et al (2011) who found that irregular use was significantly more likely in men compared with women. To our knowledge, other studies on interventions improving HA use do not report gender differences in HA outcomes.…”
Section: Control Groupsupporting
confidence: 90%
“…A similar dichotomous presentation of daily hours of use was also found in one other study . Nine studies reported a wide range of daily hours of use from none to 18 hours per day (Saunders & Jutai, 2004;Cox et al, 2005;Nabelek et al, 2006;Bertoli et al, 2009;Saunders et al, 2009;Bertoli et al, 2010; Br ä nnstr ö m & Wennerstr ö m, 2010; Hartley et al, 2010;Staehelin et al, 2011). This is evidence of the lack of consistency in the reports on the daily hours of hearing-aid usage among the studies that were included in this review.…”
Section: Hearing-aid Usage Dimensionsmentioning
confidence: 81%
“…The age of the participants of these studies ranged from 50 to 97. With the exception of two studies that had subjects as young as 15, nonetheless, 77% of the subjects in these two studies were over the age of 65 (Bertoli et al, 2009;Staehelin et al, 2011). Sample sizes varied signifi cantly across studies, ranging from 60 (Yueh et al, 2001;Saunders et al, 2009) to 14 737 (Smeeth et al, 2002).…”
Section: Data Extractionmentioning
confidence: 84%
See 1 more Smart Citation
“…Even in the general field of HAs, there has been very little research to date that examines the differences between men and women in the use of HAs [McCormack and Fortnum, 2013]. In a study by Staehelin et al [2011], women also reported a higher prevalence of daily and regular use of HAs.…”
Section: Difference Between Earsmentioning
confidence: 99%